Scientific production and research trends in accounting information systems - Delgado, Wilson Torres; Luna, Mario Alexis Grandez; Huamantumba, Edman Silva; Huamantumba, Gretel Silva; Rivasplata, Walter Chavez; Tapia, Andrea Margot Ochoa; Reynaga, Nicmar Nico García; Cerrón, Juan José Oré (Iberoamerican Journal of Science Measurement and Communication (Online), 2025)
Objective. This study aims to analyze trends in research on accounting information systems (AIS) as reflected in the Scopus database, covering the entire period during which related works have been published. To achieve this, we have identified the main characteristics and trends of research on this topic. Design/Methodology/Approach. To perform a bibliometric analysis, data were extracted from Scopus. First, data collection was carried out. For this purpose, scientific articles published between 1961 and 2024 were selected using keywords and previously defined inclusion/exclusion criteria. In this case, the document typology was delimited to analyze the results only for citable documents. Subsequently, bibliometric indicators were analyzed by calculating general metrics and mapping trends over the last ten years using the Bibliometrix tool. Results/Discussion. The analyzed distribution of author productivity was consistent with Lotka's Law, showing a concentration of scientific output among a small group of highly productive authors. Lederer AL, King WR, Grover V, and Marsden Jr. are influential figures in information systems, and their contributions are directly relevant to AIS. Trends in blockchain, information systems, and data analytics research reveal a dynamic and transformative landscape in the AIS field. These technologies are redefining the management, analysis, and protection of data in the healthcare sector. Conclusions. This study offers an overview of recent literature on AIS, emphasizing various bibliometric papers and review studies. The convergence of blockchain technology, information systems research, and data analytics is developing a more robust, secure, and intelligent AIS ecosystem.